1987
DOI: 10.1149/1.2100621
|View full text |Cite
|
Sign up to set email alerts
|

On the Solubility of Aluminum Carbide and Electrodeposition of Carbon in Cryolitic Melts

Abstract: The solubility of aluminum carbide in cryolitic melts was determined as a function of the following parameters: (i) normalNaF/AlF3 molar ratio false(CRfalse) of normalNaF‐AlF3 melts at 1020°C, (ii) temperature of normalNaF‐AlF3 melts at CR=1.80 , (iii) alumina concentration at CR=1.80 normaland 1020°C , and (iv) CaF2 concentration of normalNaF‐AlF3‐CaF2 melts at CR=1.80 normaland 1020°C . At 1020°C, a maximum concentration of 2.1 weight percent aluminum carbide was found at CR=1.80 . The followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Aluminum deposits at a more positive potential on graphite than on platinum. That is probably because the occurrence of a surface chemical reaction between aluminum and graphite in fused salt, which is probably a well-known process, i.e., the formation of aluminum carbide, 8,9,15,16 facilitates the aluminum deposition. The surface chemical reaction may be written as follows…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminum deposits at a more positive potential on graphite than on platinum. That is probably because the occurrence of a surface chemical reaction between aluminum and graphite in fused salt, which is probably a well-known process, i.e., the formation of aluminum carbide, 8,9,15,16 facilitates the aluminum deposition. The surface chemical reaction may be written as follows…”
Section: Resultsmentioning
confidence: 99%
“…A thermodynamic calculation shows that the standard decomposition potential of Al 4 C 3 is 0.145 V. Because the aluminum deposition occurs at ca 0.25 V, the anodic wave A 1 at 0.4 can be assigned to the deposition of carbon from aluminum carbide, which agrees with the reports that the carbon deposition occurred at a potential of 150 mV positive to aluminum deposition. 15,16 This anodic reaction can be expressed by Eq. 6 From the analyses mentioned above, it can be concluded that the occurrence of potassium intercalation resulted not only in the deg-radation of cathode carbon but also in the enhancement of the side reaction, which would intensively lower the current efficiency of aluminum production.…”
Section: D418mentioning
confidence: 99%
“…Wear of carbon cathode blocks used in industrial cells is one if the factors limiting the lifetime of the cathode. Two different mechanisms contribute to the wear; physical wear caused by solid alumina particles and chemical wear caused by the formation and dissolution of aluminium carbide, which is soluble in aluminium and to a larger extent in cryolite [1].…”
mentioning
confidence: 99%
“…It has also been demonstrated that the reverse reaction, i.e. the anodic deposition of carbon, may take place at low current densities on, for instance, a graphite substrate [1].…”
mentioning
confidence: 99%